INTENSITAS KOMUNIKASI INTERPERSONAL AYAH DAN ANAK LAKI-LAKI USIA 7 - 8 TAHUN DALAM KEBERHASILAN PEMBELAJARAN JARAK JAUH (STUDI KASUS DI RW 08 KELURAHAN SRIAMUR, TAMBUN UTARA, BEKASI) - BUDI SUSWANTO; TRISNAWATI KUSUMAWARDHANI (Institut Bisnis Muhammadiyah Bekasi, 2022)
The task of a father at home is not only responsible for meeting the material needs of the family, but also for the process of growth and education of children. Especially boys. One of them is by providing assistance during the Pelajaran Jarak Jauh (PJJ) process. This study aims to determine how interpersonal communication between fathers and sons aged 7-8 years in the success of the PJJ process in RW 08, Sriamur Village, Tambun Utara District, Bekasi. Data were collected through direct observation in the field, in-depth interviews with six key informants, and documentation. The research was conducted using a qualitative approach with a constructivist paradigm. The theory used is Interpersonal Communication or Interpersonal Communication proposed by R. Wayne Pace. Based on the conclusions from the results of the research conducted, a father plays a very important role in the success of the PJJ process for his son. For boys, fathers are role models in their lives. Because in terms of using technology in PJJ, dad is more responsive. In addition, the way a father communicates in a soft and motivating language, makes it easier for children to understand lessons.